Ethylenediamine grafted carbon nanotube aerogels modified screen-printed electrode for simultaneous electrochemical immunoassay of multiple tumor markers - Filik, Hayati; Avan, Asiye Aslihan; Puntar, Nilay Altas; Ozyurek, Mustafa; Gungor, Zeynep Banu; Kucur, Mine; Kamis, Handan; Dicle, Diclehan Ali (ELSEVIER SCIENCE SA, 2021)
A sensitive sandwich-model immunoassay designed for simultaneous electrochemical measurement of alphafetoprotein and carcinoembryonic antigen handling multiple-label strategy. The sandwich-model immunosensor was constructed by assembling ethylenediamine-MWCNT aerogels (EDA-CAGs), AuNPs and capture antibodies (Cp-Ab1) on the screen-printed carbon electrode (SPCE). The prepared EDA-CAG textures were analyzed using Fourier transform infrared (FT-IR), Scanning Electron Microscopy (SEM) and Energy Dispersive X-Ray Spectroscopy (EDX). In this protocol, AuNPs decorated EDA-CAG-carried Thionine (Thi) and AuNPs decorated EDA-CAG-carried Safranine O (SfO) (denoted as AuNP-Thi-EDA-CAG and AuNP-SfOEDA-CAG, respectively) were properly exploited as distinguishable signal labels, which were used to attach detection antibodies (Ab2) (anti-AFP2 and anti-CEA2), respectively. When two tumor antigens were present, a square wave voltammetry (SWV) scan displayed two well-separated signals, each signal indicated one target antigen. Observed results introduced that the square wave voltammetric peak current exhibited a good linear relationship to logarithm concentration in the ranges from 0.005 to 1.0 ng/mL for both analytes. The LoDs were 0.0015 and 0.0010 ng/mL (at signal/noise S/N = 3) for AFP and CEA, respectively. The designed sandwich-type immunosensor was applied to real serum sample analysis.
Keywords: Alpha-fetoprotein; Carcinoembryonic antigen; Immunosensor; Electrochemistry; Serum analysis; CANCER-DETECTION; 4 BIOMARKERS; SILVER; NANOCOMPOSITES; IMMUNOSENSORS; POLYMER; LEAD; Chemistry